Closure of patent foramen ovale defects using GORE® CARDIOFORM septal occluder: Results from a prospective European multicenter study. Issue 5 (15th March 2017) - Hardt, Stefan E.; Eicken, Andreas; Berger, Felix; Schubert, Stephan; Carminati, Mario; Butera, Gianfranco; Grohmann, Jochen; Höhn, Rene; Nielsen‐Kudsk, Jens Erik; Hildick‐Smith, David; Settergren, Magnus; Thomson, John D.; et al.
Abstract : Aims: The GORE® CARDIOFORM Septal Occluder (GSO) is a novel device designed for rapid and effective closure of patent foramen ovale (PFO) which has distinctive features making it suitable for a broad spectrum of anatomical variations. We report the procedural and 6 months follow‐up results of the first prospective, multicenter study using GSO. Methods and Results: This single‐arm study included 150 subjects undergoing closure of PFO in 10 European centers. In 149 out of 150 patients implantation of a GSO device was successful. One patient had a different PFO‐closure device implanted. Periprocedural complications were few including one patient with suspected transient ischemic attack, two access site bleedings, and one patient with AV‐fistula. No device embolization occurred. During the 6‐month follow‐up period one patient had a transient asymptomatic thrombus on the device and four patients (2.6%) were diagnosed new onset paroxysmal atrial fibrillation, which were successfully treated. No thrombembolic events occurred. Closure was successful in 94.2% of subjects at discharge evaluation and 96.9% at 6 months follow‐up. Conclusion: This prospective, multicenter study adds to previous published data and suggests that GSO is a versatile device for PFO closure with high procedural and closure success rates and low complication rates through mid‐term follow‐up. © 2017 Wiley Periodicals, Inc.